2021
DOI: 10.1111/ffe.13623
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the progressive failure of double‐flawed granite samples subjected to impact loads

Abstract: In this paper, the split Hopkinson pressure bar device and high‐speed camera system are applied to carry out the impact tests of fine‐grained granite samples with two parallel preexisting flaws, whose angles are 0°, 15°, 30°, 45°, 60°, 75°, and 90°. The dynamic compressive strength of the double‐flawed granite samples is affected by the flaw angle. By analyzing the experimental results, the peak strengths of the double‐flawed granite samples are in low level when the flaw angles are varying from 45° to 75°, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 38 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…Based on laboratory simulation tests, some researchers have carried out crack propagation studies of samples with different loading rates and crack angles. It is concluded that the loading rate can change the crack propagation mode, and the crack angle affects the crack initiation position of samples [4][5][6][7][8]. Some researchers carried out uniaxial compression experiments on samples with natural cracks and divided the crack propagation into two stages: microscopic particle damage and macroscopic crack propagation.…”
Section: Introductionmentioning
confidence: 99%
“…Based on laboratory simulation tests, some researchers have carried out crack propagation studies of samples with different loading rates and crack angles. It is concluded that the loading rate can change the crack propagation mode, and the crack angle affects the crack initiation position of samples [4][5][6][7][8]. Some researchers carried out uniaxial compression experiments on samples with natural cracks and divided the crack propagation into two stages: microscopic particle damage and macroscopic crack propagation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to investigate the dynamic splitting tensile mechanical properties of rock–concrete assemblies at different interface inclination angles. The current investigation indicates that the damage morphology (tensile damage, shear damage) and crack pattern (interfacial cracks, wing cracks, and secondary cracks) of the assemblies directly depend on the inclination angle of the interface, which in turn affects the strength and damage criterion of the assemblies 14,21 . Meanwhile, the presence of the interfacial structure makes the crack development more sensitive to the influence of non‐singular stresses 22 .…”
Section: Introductionmentioning
confidence: 79%
“…Besides, the specimens exhibit shear damage morphological characteristics. 21,54 In this case, the fracture surface is not necessarily along the diameter direction. The cracking of the interface causes the crack in the impact direction to extend to the interface, and the interface crack and impact crack intersect to form a cross crack.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In experiments, Zhou and Gu 15 investigated dynamic mechanical properties and cracking behaviors of persistent fractured granite under impact loading with various loading rates, and experimental results showed that the dynamic strength and energy absorption of persistent fractured granite decrease with increasing joint number. Zhou et al 16 investigated the progressive failure mechanism of double-flawed granite samples subjected to impact loads, and experimental results showed that the failure mode of the granite samples with flaw angles of 75 and 90 is tensile-shear failure, while the failure mode in the samples with their flaw angle varying from 0 to 60 is tensile failure. Liu et al 17 investigated dynamic splitting tensile properties of concrete and cement mortar using the Split Hopkinson pressure bar (SHPB).…”
Section: Introductionmentioning
confidence: 99%